ON SOME GEOMORPHOMETRIC PARAMETERS OF THE AGHSTEV RIVER BASIN OF THE RA (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
Based on digital elevation model of the Aghstev River basin, some morphometric parameters of the earth's surface (hypsometry, slope and aspect) were calculated for the first time. Spatial distribution patterns of morphometric variables at scale 1:200000 were described and mapped. Taking into account the fact that within flat areas of the river basin there is a certain relationship between the altitudes and slopes, an attempt was made to find relationship between those morphometric parameters in mountain conditions, too.
Keywords: Aghstev River; earth's surface hypsometry; slope and aspect; earth's surface angle of slope; digital elevation model